The Relationship between Supply Chain Practices Towards Customers Satisfaction of the F&B Industry in Johor - Kan Jia Xin; Hafizah Zulkipli (Research in Management of Technology and Business, 2024)
The food and beverage (F&B) sector are constantly evolving, with a greater emphasis on consumer happiness and rapid service delivery. This study investigates the dynamic interaction between supply chain practices and customer satisfaction in the F&B industry in Johor, Malaysia. The main objective is to identify the relationship between two key supply chain practices, namely information technology (IT) and postponement strategy, and their impact on customer satisfaction. A quantitative research approach was adopted using convenience sampling to gather insights from employees in the F&B industry in Johor. The research focuses on restaurant employees, drawing on their unique perspectives and experiences of supply chain management in the industry. The results of this study point out a strong and positive correlation between customer satisfaction, usage of information technology and postponement strategy in the F&B supply chain. Furthermore, the use of IT helps improve data management efficiency and facilitates agile decision-making, while postponement strategy can be more flexible to meet different customer needs. Supply chain practices are a way to help companies gain a high degree of competitive advantage. Hence, integrated supply chain practices are key drivers to improve customer satisfaction in the F&B industry.